Lipoma on the Lower Lip - Aita, Tiago Gai; Bonardi, João Paulo; Stabile, Gaykon Alex Vitti; Pereira-Stabile, Cecilia Luiz; Faverani, Leonardo Perez; Hochuli-Vieira, Eduardo (Wolters Kluwer, 2017)
Lipoma is a benign tumor of fat tissue, found frequently in subcutaneous tissues. However, oral manifestations are relatively rare. The present patient illustrates the successful treatment of a lipoma treated by complete excision of the lesion. A female patient, 75 years old, presenting lesion in the right oral vestibule where excisional biopsy was performed. The professional must diagnose this type of injury as soon as possible and treat it so that it does not take large proportions, which can result in esthetic and functional sequelae to the patient.